Motivating Users and Boosting Their IT Use — A Preliminary Study at Alfa Laval - Larkin,Reinell; Zalecki,Daniel (2005)
In this thesis we have discussed if rewards could increase IT acceptance and therein IT use. We have conducted a preliminary study at Alfa Laval in the countries of Denmark, Finland, Germany, Norway, and Sweden. We have specifically conducted telephone interviews with eleven Alfa Laval employees about their use of a Voluntary Computer System (VCS) called IB@WEB. Our main interest was in discovering the opinions of the IB@WEB users about how the introduction of rewards for IB@WEB use would motivate them to increase their system use. The results have been surprisingly diverse. Many employees do not believe that rewards would motivate them to use IB@WEB more as they thought that using the system was simply part of their job. Many users see IB@WEB as a tool and instead would prefer a system that is more attuned to their individual needs and work tasks. We were often given the response that a good system is motivation in itself. User opinions on their training needs and on the quality of the system differed depending on how much time they used IB@WEB per week. Users that felt IB@WEB’s functionality was not ideal at the time of the interview were often confident that the system would improve in the future.
Keywords: Information Technology (IT); Voluntary Computer System (VCS); motivation; rewards; employee behaviour; Informatics, systems theory; Informatik, systemteori